Beauty Mask Trade at Shopee from the Fiqh Perspective and the Consumer Protection Act - Sulthon, Muhammad Sulthon (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This study aims to analyze the trading practices of beauty masks in shopee storesdaily mask 04 Tuban Regency, East Java. Knives of analysis using Islamic Law combined with Law no. 8 of 1999 concerning Consumer Protection. This research is field research with a descriptive-qualitative approach. Data were classified into primary and secondary data through interviews. The results of the study prove that in accordance with the provisions of the contract in Islamic law, the trade meets the requirements. However, from the perspective of Law Number 8 of 1999, this trade does not meet the requirements of the law. In this law, it is explained that a trade or sale must include a label on its product packaging and there is an excessive prohibition on giving statements about the products being sold. Meanwhile, the reality on the ground shows that the shopee shopee Dailymask 04 does not include labels on the packaging and is excessive in promoting the products it sells. From the conclusion inabove, the researcher hopes that the Dailymask04 store will put a label with the contents: composition, method of use, and expiration date . So that consumers can know well the products being sold